Association of Traditional Risk Factors With Coronary Calcification in Persons With a Family History of Premature Coronary Heart Disease: The Study of the Inherited Risk of Coronary Atherosclerosis. (1st July 2001) - Valdes, Ana M.; Wolfe, Megan L.; Tate, Helen C.; Gefter, Warren; Rut, Andrew; Rader, Daniel J.
Abstract : Background: Genetic factors strongly influence the risk of coronary heart disease (CHD), but their contribution to variation in coronary atherosclerosis beyond that measured by traditional CHD risk factors is uncertain. Methods: We recruited healthy subjects with family histories of premature CHD. We assessed traditional risk factors and performed electron beam tomography (EBT) to quantitate coronary artery calcification (CAC), a marker of coronary atherosclerosis. Persons with significant risk factors that included diabetes, total cholesterol >300 mg/dL, active cigarette smoking, and poorly controlled hypertension were excluded from the study. In this paper, we report on the relationship between traditional risk factors and CAC in this cohort. Results: The incidence of coronary calcification was significantly higher in this cohort than in the population-based Rochester Heart Study. In our cohort, most traditional risk factors were significantly associated with CAC on univariate analysis. On the other hand, in stepwise logistical regression, age and triglycerides were the only predictors of variation in CAC in men and accounted for only 30% of the variation; in women, age, body mass index (BMI), and triglycerides were the only traditional risk factors significantly associated with CAC variation and accounted for 22.2% of CAC variance. Conclusions: In a cohort of subjects specifically selected for the characteristic of a family history of premature CHD, traditional risk factors accounted for less than one-third of the variation in CAC, and the most important predictors of CAC after age were plasma triglycerides. This supports the opinion that other inherited risk factors have important effects on the variation in coronary atherosclerosis and that the strategy of using EBT to phenotype clinically asymptomatic subjects with regard to coronary atherosclerosis may be a useful tool for identification of genes that are associated with CHD.